2001
DOI: 10.1042/0264-6021:3580069
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pyruvate dehydrogenase activity through phosphorylation at multiple sites

Abstract: The enzymic activity of the mammalian pyruvate dehydrogenase complex is regulated by the phosphorylation of three serine residues (sites 1, 2 and 3) located on the E1 component of the complex. Here we report that the four isoenzymes of protein kinase responsible for the phosphorylation and inactivation of pyruvate dehydrogenase (PDK1, PDK2, PDK3 and PDK4) differ in their abilities to phosphorylate the enzyme. PDK1 can phosphorylate all three sites, whereas PDK2, PDK3 and PDK4 each phosphorylate only site 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
159
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 27 publications
2
159
0
1
Order By: Relevance
“…It has been well documented that the PDH activity is rapidly regulated by reversible phosphorylation of its E1α component (Holness and Sugden, 2003; Kaplon et al, 2013; Kolobova et al, 2001). However, there were no differences in total PDH protein expression and E1α phosphorylation between WT and KO, under either fed or fasting condition although fasting induced a significant increase of phosphorylation as expected (Figure S3D).…”
Section: Resultsmentioning
confidence: 99%
“…It has been well documented that the PDH activity is rapidly regulated by reversible phosphorylation of its E1α component (Holness and Sugden, 2003; Kaplon et al, 2013; Kolobova et al, 2001). However, there were no differences in total PDH protein expression and E1α phosphorylation between WT and KO, under either fed or fasting condition although fasting induced a significant increase of phosphorylation as expected (Figure S3D).…”
Section: Resultsmentioning
confidence: 99%
“…PDHC is continuously regulated by phosphorylation and dephosphorylation (25). The phosphatase coded for by PDP1 regulates dephosphorylation, or activation, of PDHC (26). mRNA levels do not predict protein levels, but the fact that it was 1 of only 4 mRNAs that were altered is indicative of the sensitivity of pyruvate metabolism to HD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the pentose phosphate pathway (PPP), an alternative mechanism to consume glucose for energy production, showed that it is blocked by p53, in part through direct interaction between p53 and the rate-limiting enzyme, glucose 6-phosphate dehydrogenase (G6PD) (Jiang, et al 2011). p53 also negatively regulates pyruvate dehydrogenase kinase-2 (PDK2) through both transcriptional and post-translational pathways to activate the PDH complex, which converts pyruvate to acetyl-CoA to tip the balance from glycolysis to mitochondrial respiration (Contractor and Harris 2012; Kolobova, et al 2001). Finally, p53 transactivates Parkin (PARK2), a gene associated with Parkinsons disease, in order to inhibit glycolysis (Zhang, et al 2011).…”
Section: P53 Regulates Glucose Homeostasis: Glucose Transport Glycolmentioning
confidence: 99%